2003
DOI: 10.1210/jc.2002-021416
|View full text |Cite
|
Sign up to set email alerts
|

Topography and Associations of Leu-Enkephalin and Luteinizing Hormone-Releasing Hormone Neuronal Systems in the Human Diencephalon

Abstract: Although several studies indicated that leu-enkephalin controls gonadal function, the morphological substrate of this modulation is unknown. To reveal potential interaction sites between leu-enkephalin and LH-releasing hormone (LHRH) in the hypothalamus, the distribution and connections of leu-enkephalin-immunoreactive (IR) and LHRH-IR systems were examined in the human diencephalon using double-label immunohistochemistry. First the leu-enkephalin-IR and LHRH-IR neural elements were mapped, then the maps of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…These experiments established that Leu-enkephalin-IR cell bodies are concentrated in three different regions: (i) in the periventricular area of the tuberal region, (ii) in the infundibulum in the close proximity of the portal vessels, and (iii) in the medial preoptic area periventricularly (180). Leu-enkephalin-IR fibers established appositions to GnRH-IR cell bodies and dendrites mainly in the infundibulum and the median eminence (180). …”
Section: Afferent Inputs To Gnrh Cellsmentioning
confidence: 89%
See 2 more Smart Citations
“…These experiments established that Leu-enkephalin-IR cell bodies are concentrated in three different regions: (i) in the periventricular area of the tuberal region, (ii) in the infundibulum in the close proximity of the portal vessels, and (iii) in the medial preoptic area periventricularly (180). Leu-enkephalin-IR fibers established appositions to GnRH-IR cell bodies and dendrites mainly in the infundibulum and the median eminence (180). …”
Section: Afferent Inputs To Gnrh Cellsmentioning
confidence: 89%
“…The β-endorphin-IR input to human GnRH neurons is likely to arise from local sources given that the mediobasal hypothalamus contained a high number of β-endorphin-IR perikarya (178). Interestingly, while a series of immunohistochemical studies showed that GnRH neurons in front of the lamina terminalis do not receive significant input from axons containing catecholamines (179), NPY (15), SP (50), leu-enkephalin (180), and CRH (147), β-endorphin containing axons did innervate this rostral subpopulation of GnRH neurons (178). …”
Section: Afferent Inputs To Gnrh Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Although there are plenty of publications reporting the distribution of leu‐enkephalin in the rodent brain (70–73), only one study has reported the distribution of leu‐enkephalin in the human hypothalamus (74). In the human hypothalamus, the majority of leu‐enkephalin‐IR perikarya are present in the periventricular area of the hypothalamus and the infundibulum.…”
Section: Discussionmentioning
confidence: 99%
“…Most peptide neurotransmitters identified within neuronal afferents to human GnRH neurons are synthesized in distinct cell populations of the medial hypothalamus (Hrabovszky and Liposits, 2013 ) and include neuropeptide Y (Dudás et al, 2000 ), substance P (Dudás and Merchenthaler, 2002a ; Hrabovszky et al, 2013 ), galanin (Dudás and Merchenthaler, 2004a ), corticotropin-releasing hormone (Dudás and Merchenthaler, 2002b ), kisspeptin (Hrabovszky et al, 2010 , 2011 , 2012b ; Molnár et al, 2012 ), neurokinin B (Hrabovszky et al, 2011 , 2012b ; Molnár et al, 2012 ), endorphins (Dudás and Merchenthaler, 2004b ), enkephalins (Dudás and Merchenthaler, 2003 ), dynorphins (Dahl et al, 2009 ), RF-amide related peptide/gonadotropin-inhibiting hormone (Ubuka et al, 2009 ) and cocaine- and amphetamine-regulated transcript (Skrapits et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%